Answer:
24 different ways
Step-by-step explanation:
I looked it up to figure this out and that is how I got that answer.
9514 1404 393
Answer:
f(x) = -4x^2 +48x -129
Step-by-step explanation:
It usually works well to compute the square first. That is, simplify according to the order of operations.
f(x) = -4(x^2 -12x +36) +15
f(x) = -4x^2 +48x -144 +15
f(x) = -4x^2 +48x -129
The third answer option is correct. sqrt(x) = x^(1/2). So sqrt(121) = 121^(1/2).
Step-by-step explanation:
1.5/4x-1=0.4/x+4
We move all terms to the left:
1.5/4x-1-(0.4/x+4)=0
Domain of the equation: 4x!=0
x!=0/4
x!=0
x∈R
Domain of the equation: x+4)!=0
x∈R
We get rid of parentheses
1.5/4x-0.4/x-4-1=0
We calculate fractions
(1.5x)/4x^2+(-0.4*4x)/4x^2-4-1=0
We add all the numbers together, and all the variables
(+1.5x)/4x^2+(-0.4*4x)/4x^2-4-1=0
We add all the numbers together, and all the variables
(+1.5x)/4x^2+(-0.4*4x)/4x^2-5=0
We multiply all the terms by the denominator
(+1.5x)+(-0.4*4x)-5*4x^2=0
Wy multiply elements
-20x^2+(+1.5x)+(-0.4*4x)=0
We get rid of parentheses
-20x^2+1.5x-0.4*4x=0